2011
DOI: 10.1007/s10646-010-0592-y
|View full text |Cite
|
Sign up to set email alerts
|

Using chemical fractionation to evaluate the phytoextraction of cadmium by switchgrass from Cd-contaminated soils

Abstract: The purpose of this study is to evaluate the phytoextraction of cadmium (Cd) from contaminated soils by switchgrass (Panicum virgatum L.), which is a promising energy crop with high biomass. Two ecotypes of switchgrass cultivars, Alamo and Blackwell, were investigated in a pot experiment. Dry weight and plant Cd concentration of the switchgrass plants growing on Cd-spiked soils (0, 20, and 60 mg Cd kg(-1) soil) with chelating agent amendments (1 g kg(-1) citric acid [CA] and 0.1 g kg(-1) ethylene diaminetetraa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…And there were no visible symptoms of chlorosis and necrosis. The result is similar with Chen et al [29].…”
Section: Plant Growthsupporting
confidence: 92%
“…And there were no visible symptoms of chlorosis and necrosis. The result is similar with Chen et al [29].…”
Section: Plant Growthsupporting
confidence: 92%
“…It was worth noting that the proportions of exchangeable Cd obviously increased in the T2 and T3 treatments compared with those in the T1 treatment (Table 3), possibly due to the low soil pH and the addition of cadmium nitrate. Similarly, Chen et al (2011) also reported that the exchangeable Cd fraction greatly increased with increasing Cd supply in the acid Pinchen soil. As for the difference of other Cd fractions such as Fe/Mn oxide and organic matter forms between YCT and JFZ, a possible explanation could be given by considering the difference of root exudates between them.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Entry and Watrud (1998) found that 'Alamo' can accumulate 137 Cs and 90 Sr from a contaminated growth medium. In addition, two switchgrass cultivars ('Alamo' and 'Blackwell') were used to evaluate the phytoextraction of Cd by switchgrass from Cd-contaminated soils by Chen et al (2011). Reed et al (1999Reed et al ( , 2002 reported that switchgrass could accumulate Cd under low pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…and sunflower (Helianthus annuus L.) (Shahandeh and Hossner 2000). In addition, two switchgrass cultivars ('Alamo' and 'Blackwell') were used to evaluate the phytoextraction of Cd by switchgrass from Cd-contaminated soils by Chen et al (2011). The results showed that 'Alamo' is better suited for the phytoextraction of Cd from contaminated soils.…”
Section: Introductionmentioning
confidence: 99%